Interleukin-23 (IL-23) and mitogen-activated protein kinases (MAPKs) expression in murine macrophage cell line J774A.1 stimulated with recombinant bcg (rBCG) clone expressing MSP-1C of Plasmodium falciparum - Umar, Mohammad Shahrizal Mohd (Pusat Pengajian Kesihatan, 2015)
Malaria is a disease caused by a Plasmodium parasite that is transmitted by Anopheles mosquitoes. Plasmodium falciparum (P. falciparum') is the most deadly to humans. In Malaysia, malaria is still one of the most important vector-borne diseases, primarily in Sarawak and Sabah. The 19-kDa merozoite surface protein 1 (MSP-1C) of Plasmodium is a primary candidate for a malaria vaccine as it is highly immunogenic in humans. The inhibition of MSP-1C was previously proposed to be one of the possible mechanisms for the inhibition of merozoite invasion. Interleukin-23 (IL-23) is a cytokine composed of pl9 and p40 subunits which involve in the stimulation of memory CD4+ T cells. The mechanism of IL-23 regulation has been shown to be dependent on signalling molecules known as Mitogen- Activated Protein Kinases (MAPKs) which consist of the p38, extracellular signal-regulated kinase (ERK), and c-Jun N-tenninal kinase (JNK). This study was conducted to determine IL-23 expression by ELISA followed by the detection of signalling pathways activated by Western Blot analysis in macrophages stimulated with rBCG. Macrophage cell line J774A.1 were incubated in DMEM with 10% FBS. The cell was stimulated with BCG and rBCG for 24 and 48 hours. For each incubation time, flasks containing macrophage cultures were scrapped and centrifuged. The supernatant were collected for ELISA analysis while the cell pellets were collected for Western Blot analysis. ELISA result shows that there is an increase of IL-23 expression from 24 to 48 hours; however statistical analysis shows no significant difference. For signalling molecules, only ERK was found to be induced by rBCG stimulation, but not for p38 and JNK. As a conclusion, IL-23 expression is induced in response to rBCG stimulation and it is dependent on ERK signalling molecules.